Global disorders of consciousness. Issue 2 (20th December 2013) - Bayne, Tim; Hohwy, Jakob
Abstract : In recent decades there has been a great deal of interest in global disorders of consciousness, such as the vegetative state, the minimally conscious state, and epileptic absence seizures. Global disorders of consciousness pose significant challenges to consciousness science in that the ordinary pretheoretical criteria for the ascription of consciousness are not easily applied in such contexts, and it is often unclear what kinds of conscious states—if any—patients are in. At the same time, global disorders of consciousness also promise to reveal a great deal about the nature of consciousness and the relationship between consciousness and cognitive and behavioral control. WIREs Cogn Sci 2014, 5:129–138. doi: 10.1002/wcs.1270 This article is categorized under: Philosophy > Consciousness